1990
DOI: 10.1007/bf02624103
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ethanol on rat schwann cell proliferation and myelination in culture

Abstract: It is possible to treat dissociated embryonic rat dorsal root ganglia in culture to inhibit proliferation of all nonneuronal cells except Schwann cells. Neurons have been shown to produce a mitogenic stimulus for Schwann cells under these conditions. Additionally, myelin-competent neurons induce Schwann cells to elaborate myelin sheaths. Groups of sibling cultures were exposed to various nonlethal concentrations of ethanol (0, 43, 86, or 172 mM) for 4 wk. Cultures were assessed weekly by light microscopy in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Histological evidence showed patchy demyelination of motor and mixed nerves, suggestive of Schwann cell dysfunction 8, 9. This finding was supported by an in vitro study of the effects of ethanol in rats, which showed that ethanol affected both Schwann cell proliferation and myelin formation 41. These findings imply different structural targets of ethanol in the development of ALN that can lead to either an axonal‐ or a demyelinating‐predominant picture.…”
Section: The Ethanol Storymentioning
confidence: 70%
“…Histological evidence showed patchy demyelination of motor and mixed nerves, suggestive of Schwann cell dysfunction 8, 9. This finding was supported by an in vitro study of the effects of ethanol in rats, which showed that ethanol affected both Schwann cell proliferation and myelin formation 41. These findings imply different structural targets of ethanol in the development of ALN that can lead to either an axonal‐ or a demyelinating‐predominant picture.…”
Section: The Ethanol Storymentioning
confidence: 70%
“…Our patient, like others described both in esophageal GCT only or in those associated with cancer, had a history of alcohol abuse; the incidence seems high and may indicate a relationship, based on the evidence of ethanol's influence on Schwann cell proliferation and myelin formation in vitro 16 . Moreover, alcohol is also implied in the pathogenesis of squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Such inhibition is also evident among Schwann cells (Mithen et al, 1990), neuroblastoma cells (Luo and Miller, 1997), and neurons (e.g., in vivo: Miller, 1989Miller, , 1999Miller and Kuhn, 1995;Miller and Nowakowski, 1991;in vitro: Jacobs and Miller, 2001). The similar response of both cell types to TGF␤1 and ethanol suggests that the inhibitory effects are mediated through the same signal transduction pathway.…”
Section: Effect Of Ethanol On Tgf␤1-mediated Inhibitionmentioning
confidence: 99%